Contra el propio canon : Borges en el Laboratorio de Traducción - Delfina Muschietti (Cuadernos LIRICO)
This article can be read within the frame of a New School of Poetry Translation, following the Walter Benjamin and Giorgio Agamben theoretical premises that lead us to a New Interdisciplinary Philology. In order to translate the poem a new form must be found -like Benjamin says-, able to capture from the original its way-of-saying ; or, I add, its way-of-repeating.The reader must increase his capacity to read the intensities that come from the repetition, going through moving positions (the poet, the critic-translator-writer), that interconnect different cultural horizons and tendencies referred to language. He must adopt a flouting attention (Freud’s term), free from cultural prejudices and reading habits in order to apprehend the “estrangement” drawn by the original : a rhythmical map or flouting score, which means the track written from the contact between the poet and the flouting platform (a plain of qualitative abstraction or deleuzian transcendental immanence) where the super-refined ears (Emerson) reach the unknown. From these premises we read the lateral texts of Borges (short readings, introductions, conferences), where we see him working on the Translation Laboratory, as a translator or as a reader of other’s translations : we find a surprising contra-canon, which contradicts his known and widely spread statements about the notions of author and original.